Multiphoton Laser Microscopy and Fluorescence Lifetime Imaging for the Evaluation of the Skin. (28th November 2011) - Seidenari, Stefania; Arginelli, Federica; Bassoli, Sara; Cautela, Jennifer; French, Paul M. W.; Guanti, Mario; Guardoli, Davide; König, Karsten; Talbot, Clifford; Dunsby, Chris
Abstract : Multiphoton laser microscopy is a new, non-invasive technique providing access to the skin at a cellular and subcellular level, which is based both on autofluorescence and fluorescence lifetime imaging. Whereas the former considers fluorescence intensity emitted by epidermal and dermal fluorophores and by the extra-cellular matrix, fluorescence lifetime imaging (FLIM), is generated by the fluorescence decay rate. This innovative technique can be applied to the study of living skin, cell cultures and ex vivo samples. Although still limited to the clinical research field, the development of multiphoton laser microscopy is thought to become suitable for a practical application in the next few years: in this paper, we performed an accurate review of the studies published so far, considering the possible fields of application of this imaging method and providing high quality images acquired in the Department of Dermatology of the University of Modena.